2018
DOI: 10.1073/pnas.1813593115
|View full text |Cite
|
Sign up to set email alerts
|

Species groups distributed across elevational gradients reveal convergent and continuous genetic adaptation to high elevations

Abstract: Although many cases of genetic adaptations to high elevations have been reported, the processes driving these modifications and the pace of their evolution remain unclear. Many high-elevation adaptations (HEAs) are thought to have arisen in situ as populations rose with growing mountains. In contrast, most high-elevation lineages of the Qinghai-Tibetan Plateau appear to have colonized from low-elevation areas. These lineages provide an opportunity for studying recent HEAs and comparing them with ancestral low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
74
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 56 publications
(77 reference statements)
17
74
0
3
Order By: Relevance
“…Dating analysis suggests an origin of the spiny frogs ( Quasipaa , Nanorana ) in the Lower Miocene (23 Ma, 95% HPD 11–35 Ma; Figure and Appendix 7). This date is consistent with a transcriptome‐based study (Sun et al, ) and only slightly younger than the date reported by Che et al () who also recovered an Early Miocene or late Oligocene origin of these spiny frogs with an estimate of 22 Ma (12–34 Ma) and 27 Ma (19–36 Ma), respectively, but are approximately 15 million years younger than dates recovered by Bossuyt, and Roelants and colleagues (Bossuyt et al, ; Roelants, Jiang, & Bossuyt, ; Appendix ). We found that both genera, Nanorana and Quasipaa , diversified in the Mid‐ to Late Miocene/Early Pliocene, although Che et al () date this radiation to the Early to Mid‐Miocene.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Dating analysis suggests an origin of the spiny frogs ( Quasipaa , Nanorana ) in the Lower Miocene (23 Ma, 95% HPD 11–35 Ma; Figure and Appendix 7). This date is consistent with a transcriptome‐based study (Sun et al, ) and only slightly younger than the date reported by Che et al () who also recovered an Early Miocene or late Oligocene origin of these spiny frogs with an estimate of 22 Ma (12–34 Ma) and 27 Ma (19–36 Ma), respectively, but are approximately 15 million years younger than dates recovered by Bossuyt, and Roelants and colleagues (Bossuyt et al, ; Roelants, Jiang, & Bossuyt, ; Appendix ). We found that both genera, Nanorana and Quasipaa , diversified in the Mid‐ to Late Miocene/Early Pliocene, although Che et al () date this radiation to the Early to Mid‐Miocene.…”
Section: Resultssupporting
confidence: 89%
“…Based on our data, first the subgenus Chaparana (distribution areas F , H ; Figure a) split from Nanorana + Paa (18 Ma, 8–30 Ma), followed by the separation of Nanorana (Tibetan Plateau) from Paa (Greater Himalaya) around 9 Ma (3–16 Ma). The latter divergence estimate is considerably younger than that recovered by Che and colleagues (Che et al, ) but close to the date calculated by Sun et al () (13 Ma, 7–25) and Wiens et al () (10–12 Ma) (Figure and Appendix ).…”
Section: Resultssupporting
confidence: 86%
“…Elevation divergence might drive genetic differentiation of animal species. For instance, Sun et al (2018) detected that signals of genetic adaptation to high elevation increased from low-middle-elevation frogs and lizards to the high-elevation groups [12]. Our results also indicated this trend in the closely related toad tadpoles.…”
Section: Signals Of High-elevation Adaptation Increasing With Elevatisupporting
confidence: 73%
“…This also indicated the continued genetic evolution along the increasing elevations in the toads. Interestingly, XRCC6 was also screened as the candidate gene that is likely linked to adaptation to the high elevations in Nanorana phrynoides [12]. Furthermore, XRCC3 and XRCC4 are screened as the candidate genes that are likely linked to adaptation to the high elevations in Phrynocephalus erythrurus [58].…”
Section: Signals Of High-elevation Adaptation Increasing With Elevatimentioning
confidence: 99%
“…啮齿目高原鼠兔; 爬行类沙蜥; 两栖类倭蛙 编码基因趋同; 肠道微生物趋同 金丝猴属三个高海拔物种中有6个与高海拔适应相关的DNA损伤修复、血管生成 等高海拔适应相关功能基因存在氨基酸平行替换 [23] ; 藏獒、藏土狗群体在高原低氧适应性起重要作用的EPAS1基因表现出强烈选择信 号, 与藏族人群表现出分子水平趋同演化模式 [24] ; 藏羚羊和高原鼠兔在应对低氧状态的7个基因存在趋同信号, PKLR和NOS3在能量 代谢和心血管稳定中起作用 [25] ; 藏羚羊和牦牛在能量代谢、低温响应、紫外防护等相关基因发生加速演化, 其中 与血氧系统相关的SOCS4基因在藏羚羊与牦牛之间表现出较强的趋同演化信号 [26] ; 沿2000~4500 m海拔梯度分布的爬行类沙蜥属和两栖类倭蛙属, 在氧化应激、低氧 应答等高海拔适应相关功能和通路上表现出趋同 [27] ; 高海拔牦牛、藏绵羊相对于低海拔牛、绵羊在瘤胃微生物群落结构组分、挥发性 脂肪酸产出等功能表现出趋同性 [28] 地下洞穴极端 环境 滨鼠科、鼹形鼠科、 金毛鼹科、鼹科; 高原鼠兔、高原鼢鼠、 裸鼹鼠 编码基因趋同; 非编码基因表达 调控趋同; 基因表达模式趋同 39种哺乳动物比较基因组分析显示, 其中4种鼹鼠类哺乳动物在眼睛发育和皮肤发 育相关功能基因表现出加速演化, 与地底环境适应产生的视力和皮肤功能特化的 趋同表型相关. 在4种鼹鼠晶状体发育相关基因Pax6的增强子区域检测到演化速率 加快的趋同信号, 与地下黑暗环境选择压力放松引起的视觉衰退表型相关 [29] ; 对高原鼠兔、裸鼹鼠在内的共7个物种进行基因组分析比较, 发现高原鼠兔与裸鼹 鼠有787个基因存在氨基酸平行替换, 主要功能富集在低氧、氧含量稳态、红细胞 稳态, 血管生成和发育、呼吸管发育、ATP酶活性等低氧适应相关功能 [30] ; 对高原鼢鼠和裸鼹鼠转录组分析发现, 地下类群(高原鼢鼠、裸鼹鼠)比地上类群 (小鼠、豚鼠)具有更相近的基因趋同表达模式, 上调表达基因集中在心脏功能、低 氧适应、DNA损伤修复、骨骼肌等与地下生活适应的相关功能 [31] 海洋极端环境 鲸目; 鳍脚亚目; 海牛目 编码基因趋同 通过对三类海洋哺乳动物类群进行基因组分析, 发现其中与骨形成、骨骼肌收 缩、甲状腺机能亢进、心肌形成、调节血管收缩、调节凝血及脂肪酸氧化等相关 的基因发生了氨基酸平行替换, 并受到了正选择作用 [32] ; 在感官系统、肌肉功能、 皮肤和结缔组织、肺功能、脂代谢等方面发生加速演化 [ ; 海洋哺乳动物类群中参与ω-6多不饱和脂肪酸代谢的PON1基因在演化中丢失, 该 基因丢失趋同性状与海洋哺乳动物经历植食性到肉食性的剧烈转变相关 [35] ; 47个物种粪便样品的宏基因组测序分析结果显示, 相同食性各物种的肠道微生物 的结构组分表现出趋同, 具有高度特化食性的蚁食性哺乳动物的肠道微生物结构 组分聚类在一起表现出趋同特征 [14,36] ; 肉食性哺乳动物在控制食欲、维持血糖、毒素降解等功能基因表现出趋同丢失, 植食性哺乳动物在脂质代谢、胰蛋白酶分泌等功能基因表现出趋同丢失, 表明相 同食性类群演化出由食性驱动产生的趋同表型 [ 替换(parallel substitution)两种模式 [41] .…”
unclassified